Legislative Approaches to Drug Rehabilitation: A Socio-Legal Analysis of Policies Supporting the Reintegration of Former Addicts into Society - Widoyoko, Wredha Danang; Ngaisah, Siti; Rahmawati, Diah Ayu; Haryono, Haryono; Kurniawan, Bagus Ananda (Westscience Press, 2024)
This study explores the legislative frameworks governing drug rehabilitation and the reintegration of former drug addicts into society through a normative juridical analysis. The research examines how laws and policies influence the recovery journey, highlighting critical gaps in anti-discrimination measures, public health integration, and societal reintegration mechanisms. Comparative case studies from countries with progressive approaches, such as Portugal and Norway, illustrate effective models for aligning legal systems with public health strategies. The findings emphasize the need for legislative reforms that promote inclusivity, support long-term recovery, and foster societal acceptance. Recommendations include expanding anti-discrimination protections, incorporating restorative justice mechanisms, and enhancing interagency collaboration to ensure holistic rehabilitation programs. This research contributes to the discourse on aligning law and social policy to address the multifaceted challenges of drug addiction and reintegration.